Shu’ubiyya Thoughts of Muwallads in Andalusia: The Causes and Contexts - Mir, Mohammad Ali; Farahmand, Yoones (Journal of History Culture and Art Research, 2017)
Abstract Muwallads (native neo-Muslims) were one of the groups that played an important role in political and social changes during the reign of the Umayyads of Andalusia. By conversion to Islam, they called for equal rights with the Arab minority. However, political exclusion, poverty, and economic pressure, social and racial discrimination applied against them by the Arab Umayyad rulers provided the context of their rebellion. Initially, most Muwallads began military struggle against the reign to obtain their rights. The conditions almost changed by the beginning of the third Abul Al-Rahman’s governance (imprinted, 912-961 AD), and the peaceful politics as well as ethnic and religious tolerance of Abdul Nasser, the Umayyad caliph and his son, the second sentence (imprinted; 961-972 AD) made opportunities for Muwallads to participate in political and social structures of Andalusia society. However, in the meantime, some of them emphasizing their ethnic identity did cultural and intellectual activities in the form of praising and advocating talent and ability of non- Arab against Arabs’ racial prejudice and racial superiority. In addition, gradually, with the weakness of the Umayyad rule in Andalusia and the formation of independent states, the defensive mode changed into offensive and explicit denial of the Arab’s race by the Muwallads that culminated in the Shu’ubiyya treatise of Ibn Garasiah. Using an analytical approach, this article is intended, first, to examine the causes and context of the formation of Shu’ubiyya thoughts in Andalusia and then to survey the method and quality of writing treatises and writings of Shu’ubiyya at the end of Umayyad rule.